Failure analysis of tire separation in two-sized tires on Airbus planes. (March 2016) - Xie, Mingli; Tang, Haijun; Yao, Hongyu
Abstract: Two-sized radial tires from a famous brand have been installed on Airbus planes. Several times, tread throw failures have occurred with these types of tires. Laboratory observations showed that these two-sized tires feature two cut-type belt plies (belt plies with cut cord ends lined at either edge). These are the 7th and 8th belt plies and, on all failed tires, separation occurred at the cut cord ends of the 7th belt plies. Because the cut cord ends of the 7th and 8th belt plies were not chemically pre-treated after the fabric ply was cut to get belt ply strips, the adhesion strength between the rubber and the cut cord ends decreased significantly. This means that micro-cracks initiated easily around the cut cord ends of the 7th and 8th belt plies. Due to the structural effect of these two-sized tires, there was uneven wear on their treads with the third ribs having the maximum amount of remaining thickness. Uneven tread wear resulted in a higher load at the third ribs. This generated higher temperatures around the edge of the 7th belt ply at the later stages of one life cycle. The higher temperatures decreased the strength of the local rubber and sped up the rubber's aging process. The higher loads experienced around the edges of the 7th belt ply and transferred from the third rib, and the decreased mechanical properties of the rubber at that location (due to higher temperatures), ultimately sped up micro-crack formation and expansion at the cut cord ends of the 7th belt ply. This finally led to premature tire failure. The tire manufacturer is currently taking measures to modify the structure of these two-sized tires in order to avoid uneven wear and hopefully prevent such failures in the future. Highlights: we find the common failure mode for these two size aircraft tires. It is pointed out that edges of two cut type belt plies are weaker locations of these two size tires. we put forward the mechanism for this common failure mode. It is disclosed that uneven wear is a cause speeding up microcracks initiation and growth in the tires.